Pathogenicity of local isolates of Mycoplasma ovipneumoniae and Mycoplasma arginini in experimental West African Dwarf goats - Akwuobu, Chinedu Adive; Chah, Kennedy Foinkfu; Oboegbulem, Stephen Ike; Rabo, Jude S. (Journal of Advanced Veterinary and Animal Research, 2016)
Objective: This study was carried out to assess the pathogenicity of local isolates of Mycoplasma ovipneumoniae and M. arginini in West African dwarf goats (kids) in Nigeria. Materials and methods: A total of 22 goats aged less than 1-year were purchased from markets. The goats were divided into six groups comprising of four experimental groups (EG; 4 in each) and two control groups (CG; 3 in each). The goats were fed ad libitum with standard diets and safe water. Groups EG1 and EG2 were infected with M. ovipneumoniae through trans-tracheal (TT) and intravenous (IV) routes, respectively, while those in groups EG3 and EG4 were infected with M. arginini through the same routes. Goats in groups CG1 and CG2 were inoculated with sterile Mycoplasma broth through TT and IV routes, respectively. In all cases, the amount of bacteria inoculated was 1.5x108 cells/mL. After the onset of the disease in goats, re-isolation of Mycoplasma was performed by culturing on mycoplasma agar supplemented with mycoplasma supplement G. The goats were monitored for 14 days post-infection (PI) to observe respiratory signs and mortality. Post-mortem (PM) examination was performed on each animal that died, while one surviving goat from each of the groups was sacrificed at 14 days PI for PM. After PM, histopathology was performed to observe the changes in tissues. Results: Cough and nasal discharges were observed in all the experimentally infected goats seven days PI. Mortalities were recorded in goats in EG1 (two goats), EG2 (one goats), EG3 (two goats) and EG4 (one goat). At PM, pneumonic lesions were observed in the lungs of all the experimentally infected goats. Conclusion: This study provides evidence that the local isolates of M. ovipneumoniae and M. arginini strains are pathogenic for goats in Nigeria. http://doi.org/10.5455/javar.2016.c161